Deciphering PPAR-inducing pathway clarifying the link between Alzheimer's Disease and diabetes - Nesma S Shafie; Yasser M Morsy; Marwa Amer (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2023)
Diabetes is a widely prevalent metabolic disorder characterized by chronic hyperglycemia. This condition is caused by various factors that ultimately result in pancreatic β cell failure. The American Diabetes Association (ADA) recognizes two main types of diabetes: Type 1 diabetes mellitus (T1DM) and Type 2 diabetes mellitus (T2DM) [1-4].